The Influence Of Financial Literacy On The Financial Performance Of Small Businesses In Makassar City - Windi Citra; Sultan Sarda; Nasrullah, Nasrullah (CV. AFDIFAL MAJU BERKAH, 2024)
Windi Citra, 2024. The Influence of Financial Literacy on the Financial Performance of Small Businesses in Makassar City. Thesis. Department of Management, Faculty of Economics and Business, Muhammadiyah University of Makassar. Supervised by Sultan Sarda and Nasrullah. This research aims to determine the effect of financial literacy on the financial performance of small businesses in the city of Makassar. The population in this research is all small businesses recorded in the Makassar City Cooperatives and SMEs Department in 2022, namely 136 businesses. The type of data used in this research is quantitative data obtained from questionnaires distributed to 58 samples related to the problem being researched. Data were analyzed using a simple regression analysis method with the help of SPSS data processing to prove the hypothesis. The t test shows that the t-count > t-table value is 6.681 > 1.6725. Meanwhile, the significance value of the financial literacy variable is 0.000 <0.05. So it can be concluded that financial literacy has a positive and significant effect on business financial performance. The better the level of financial literacy of business actors, the better the resulting performance will be.